Yogyakarta : Jendral Spoor (Operatie Kraai) versus Jendral Sudirman (Perintah Siasat no. 1) - Soetanto, Himawan, 1929- (Jakarta : PT Gramedia Pustaka Utama, 2006)
History of Indonesian revolution against Dutch military aggression on December 19, 1948 in Yogyakarta
Daftar pustaka : p. 377-388
Keywords: Yogyakarta (Indonesia) -- Politics and government; Yogyakarta (Indonesia) -- History